2022
DOI: 10.12688/f1000research.74385.2
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among positive and negative symptoms, neurocognition, social cognition, and functioning in clinically stable patients with schizophrenia: a network analysis

Abstract: Background: Schizophrenia has a broad range of interrelated symptoms and impairment in functioning. The objective of the study was to explore the interplay between positive symptoms, negative symptoms, neurocognition, social cognition and functional outcome in patients with schizophrenia using network analysis. Methods: Participants were 64 clinically stable patients with schizophrenia. Psychopathologic, neurocognition, social cognition, and functional outcome were measured using the Scale for the Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Third, a network analysis did not analyze other important predictors of social functioning, e.g., those related to social cognition and metacognition. Nevertheless, it is important to note that impairments of social cognition and metacognition might be the consequence of neurocognitive de cits (10,11,12). Therefore, it is likely that inclusion of these variables would not change considerably the centrality measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a network analysis did not analyze other important predictors of social functioning, e.g., those related to social cognition and metacognition. Nevertheless, it is important to note that impairments of social cognition and metacognition might be the consequence of neurocognitive de cits (10,11,12). Therefore, it is likely that inclusion of these variables would not change considerably the centrality measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis of studies performed in people with early psychosis demonstrated that impairments across all domains of neurocognitive performance and social cognition are associated with lower psychosocial functioning both cross-sectionally and longitudinally (9). However, there is evidence that neurocognitive de cits might affect social functioning through the effects on social cognition (10,11,12). Other factors that have been associated with lower social functioning include earlier age of psychosis onset (13) and longer duration of untreated psychosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the treatment of schizophrenia has primarily focused on managing hallucinations and delusions, while negative and cognitive symptoms have proven more challenging to address than positive symptoms[16].However, numerous previous studies have underscored that negative and cognitive symptoms serve as the most robust predictors of functional outcomes in schizophrenia [17][18][19]. Consequently, targeted improvement of patients' negative symptoms may lead to concurrent enhancements in cognitive impairment symptoms.…”
Section: Discussionmentioning
confidence: 99%